2007
DOI: 10.1089/jir.2006.0131
|View full text |Cite
|
Sign up to set email alerts
|

Measured Neutralizing Titers of IFN-β Neutralizing Antibodies (NAbs) Can Depend on the Preparations of IFN-β Used in the Assay

Abstract: An immune response to recombinant human protein therapeutics, including type I interferons (IFNs), has the potential to have a serious negative impact on safety and efficacy. Monitoring of patients for neutralizing antibodies (NAbs) often is advisable. In the case of IFN-beta therapy for multiple sclerosis (MS), we obtained reproducible quantitative titers of NAbs using an improved and well-characterized assay based on a 10-fold reduction of a challenge dose of IFN-beta. However, the observed titer was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In the presence of a sufficient concentration of NAbs, IFN beta does not up-regulate MxA protein levels, which are measured by an enzyme-linked immunosorbant assay (ELISA). This assay is a highly sensitive, specific, and simple method for measuring anti-IFN beta NAbs [11,12]. While the results of these two assays were generally concordant, significant scatter was observed when the same serum samples were analyzed using both assays (Fig.…”
Section: Nab Assaysmentioning
confidence: 85%
See 1 more Smart Citation
“…In the presence of a sufficient concentration of NAbs, IFN beta does not up-regulate MxA protein levels, which are measured by an enzyme-linked immunosorbant assay (ELISA). This assay is a highly sensitive, specific, and simple method for measuring anti-IFN beta NAbs [11,12]. While the results of these two assays were generally concordant, significant scatter was observed when the same serum samples were analyzed using both assays (Fig.…”
Section: Nab Assaysmentioning
confidence: 85%
“…Choice of the appropriate sensitivity and cutoff value, which may differ for different IFN betas, is an unfortunately circular process. Clinical observations of worsened outcome may assist in determining the appropriate NAb assay sensitivity and cutoff values, but improper initial choice of these values may prevent observation of NAbrelated clinical changes [12,14]. Fig.…”
Section: Nab Assay Sensitivitymentioning
confidence: 99%
“…Most investigators have found it simpler to use IFNβ-1a antigen as the target in antibody assays, even in patients who are receiving IFNβ-1b. This leads to overestimation of antibody levels in patients treated with IFNβ-1b compared with what would be determined using IFNβ-1b as the antigen [69]. Generally, however, antibody titers are higher in patients treated with IFNβ-1a, regardless of whether titers are assessed against IFNβ-1a or IFNβ-1b.…”
Section: Factors Confounding Cross-study Comparisons Of Interferon Bementioning
confidence: 95%
“…The ten-fold reduction approach has been successfully operative with very different methodologies to measure NAbs to the IFNs, involving different biological effects, whether they be, for example, antiviral (Grossberg and others 1986), MxA protein induction (Pungor and others 1998;Files 2007), cell-growth inhibition (Redlich and Grossberg 1989), or luciferase reporter gene induction (Lallemand and others 2008;Lam and others 2008). Further, NAb titers calculated as TRU/mL determined on the same serum samples by the luciferase gene induction and by antiviral assays were comparable (Lallemand and others 2008).…”
Section: Figmentioning
confidence: 99%